Normes hematologiques du Zebu Gudali dans les hauts-plateaux du Nord-Ouest camerounais - Merlin, P. (1986)
The purpose of the study was to determine some standard blood constituents of Gudali cattle raised in the north-west province of Cameroon. Two series of blood samples were succesively taken from 189 and 141 male and female cattle to determine the leucocytic and erythrocytic values. No significant differences were observed between female and male cattle. The red blood cell count averaged 8.5 million/mm³. The RBC decreased with age while the packed cell volume remained constant and averaged 34.9. The mean corspuscular volume was 37 for 1 to 3 year-old cattle and 43 for cattle above 3 years. During the first two years the number of leucocytes was 12,300 decreasing afterwards to 10,000. The number of neutrophils was about 2,820. That of eosinophils was 241 for the first year, 913 for the second year and 1,658 beyond two years. The number of lymphocytes varied from 7,750 for the first year to 3,810 in the 13th year following an exponential regression. Standards established were away from the mean by 1.96 time the standard deviation. The results were compared with three other studies carried in West Africa.